Fabrication and performance of a power generation device based on stacked piezoelectric energy-harvesting units for pavements. (1st May 2018) - Wang, Chaohui; Wang, Shuai; Li, Qiang Joshua; Wang, Xingju; Gao, Zhiwei; Zhang, Lu
Highlights: A device is designed based on stacked piezoelectric energy-harvesting units for pavements. The performance of the device is evaluated based on the real road environment. The durability of the device is tested and verified, followed by future research plan. Abstract: Although piezoelectric power generation for pavements is technically feasible, harvesting energy in a stable and efficient manner still presents several challenges. This paper designs and assesses stacked piezoelectric energy-harvesting power generation devices for pavements, in which energy output and road coupling are considered. Following corresponding technical specifications, the dimensions of the proposed power generation device are determined, and the unit is assembled for subsequent testing in terms of its electrical energy outputs. The energy outputs are analyzed in various series and parallel configurations of the units, different loads, and frequency conditions. Results indicate that power generation device with the dimension of 100 mm × 100 mm achieves optimal power generation outputs. The electrical output is positively correlated to the number of parallel piezoelectric energy-harvesting units, the magnitude of load, and the frequency of traffic action. The maximum output at the 0.2 MPa load magnitude and 10 Hz load frequency is 0.88 mW, and the corresponding optimum load is 20 kΩ. The maximum output at the 0.7 MPa and 15 Hz load level can reach up to 11.67 mW, and the corresponding optimum load is 10 kΩ. Subsequently, Mechanical Testing and Simulation (MTS) is performed with 40, 000 load cycles, and the overall deformation of the power generation device is minimal and the electrical outputs of the piezoelectric energy-harvesting units remain stable. Finally, future research plan is discussed.